Effectiveness Of Leukoreduction And Washed Packed Red Blood Cells on Hemoglobin Increment And Side Effects In Post Transfusion Anemia Patients - Gatot, Dairion; Mardia, Andri Iskandar (Buletin Farmatera, 2021)
Blood transfusion is one of the methods to treat anemia and packed red blood cells (PRC) are the most widely used blood component. Post transfusion results showed that increment of hemoglobin (Hb) does not always match the amount of PRC given. This is thought to be due to the recipient's immune reaction to the PRC component. Leukoreduction is an action to reduce leukocytes from the PRC component thereby reducing the risk of an immune reaction. Alternatively, another method called washed PRC can also be used. In this study, the researcher studied the effectivity of leukoreduction and washed PRC on Hb increase in post-transfusion anemia patients compared with the usual PRC. The researcher used a pre-test post-test group design method of 60 people who were divided into 3 groups (ordinary PRC, washed PRC, leukofiltered PRC). The results showed all three groups reached the transfusion target (a 75% increase in Hb) and there were no differences among the groups both in terms of achievement of the Hb target and the incidence of side effects. There were no differences in the success of transfusion and incidence of side effects among the three groups.